Bridging the Knowledge Gap on Iron Deficiency Anemia Among Nursing Students: Menjembatani Kesenjangan Pengetahuan tentang Anemia Defisiensi Besi di Kalangan Mahasiswa Keperawatan - Zahraa Mahmoud Hussain Al-Hejaj (Academia Open, 2024)
Background: Iron deficiency anemia (IDA) is a prevalent nutritional disorder characterized by a significant reduction in the body’s iron stores, affecting oxygen transport and leading to various health complications. Specific Background: The understanding of IDA among nursing students is underdeveloped, especially regarding the differences between morning and evening study cohorts. Knowledge Gap: Understanding nursing students' knowledge of IDA is critical for enhancing educational strategies and improving patient care, yet limited studies have assessed this demographic's awareness of the condition and its management. Aims: This study aims to evaluate nursing students' knowledge about IDA and to compare the levels of knowledge between morning and evening students at the College of Nursing, University of Basrah, over a six-month period from November 2023 to March 2024. Results: A descriptive cross-sectional study was conducted involving 145 students (72 morning and 73 evening) who completed a questionnaire. Results indicated that 40.2% of morning students and 53.4% of evening students suffered from iron deficiency. While 86.1% of morning students had prior knowledge of IDA compared to 67.1% of evening students, the mean knowledge levels were deemed good for both groups, with no significant statistical difference between them. Novelty: This research contributes to the existing literature by highlighting knowledge levels of IDA among nursing students in Iraq, revealing that both morning and evening cohorts possess substantial understanding yet exhibit slight discrepancies. Implications: The findings underscore the necessity for targeted educational interventions to bridge the knowledge gap regarding IDA, ultimately enhancing nursing students' competencies in managing this condition in clinical settings. Highlights: IDA Prevalence: 40.2% morning students and 53.4% evening students affected. Knowledge Difference: 86.1% morning vs. 67.1% evening students aware of IDA. Educational Need: Targeted interventions required for improved IDA management in nursing education. Keywords: Iron deficiency anemia, nursing students, knowledge assessment, educational interventions, Iraq